2016
DOI: 10.1242/dev.131912
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes production of neural crest cells in the embryonic head

Abstract: Hypoxia is encountered in either pathological or physiological conditions, the latter of which is seen in amniote embryos prior to the commencement of a functional blood circulation. During the hypoxic stage, a large number of neural crest cells arise from the head neural tube by epithelial-to-mesenchymal transition (EMT). As EMTlike cancer dissemination can be promoted by hypoxia, we investigated whether hypoxia contributes to embryonic EMT. Using chick embryos, we show that the hypoxic cellular response, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 97 publications
6
52
0
Order By: Relevance
“…Previous studies have shown that HIF1α and its downstream effector CXCR4 both up‐regulate proliferation of various tumor and progenitor cells (Carmeliet et al, ; Goda et al, ; Kahn et al, ; Nombela‐Arrieta et al, ; Park et al, ; Xia et al, ; Guimaraes‐Camboa et al, ), and also up‐regulate chemotaxis, migration, and EMT of neural crest stem/progenitor cells in zebrafish, Xenopus and chick embryos as well as mouse hair follicles (Belmadani et al, ; Rezzoug et al, ; Barriga et al, ; Singleton Escofet, ; Scully et al, ). Hence, we were interested in analyzing HIF1α and CXCR4 expression in rNCSCs under various oxygen tensions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that HIF1α and its downstream effector CXCR4 both up‐regulate proliferation of various tumor and progenitor cells (Carmeliet et al, ; Goda et al, ; Kahn et al, ; Nombela‐Arrieta et al, ; Park et al, ; Xia et al, ; Guimaraes‐Camboa et al, ), and also up‐regulate chemotaxis, migration, and EMT of neural crest stem/progenitor cells in zebrafish, Xenopus and chick embryos as well as mouse hair follicles (Belmadani et al, ; Rezzoug et al, ; Barriga et al, ; Singleton Escofet, ; Scully et al, ). Hence, we were interested in analyzing HIF1α and CXCR4 expression in rNCSCs under various oxygen tensions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that S100A2 may compete with F‐actin for binding to tropomyosins in microvilli in the cytoplasm of LLC PK1 cells (Gimona et al, ), and cell stretching/extension was significantly reduced by treatment with HIF1α‐stabilizing chemical compounds (Scully et al, ). Because we observed significantly increased HIF1α expression in the rNCSCs cultured at 0.5% O 2 (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In ontogenesis, hypoxic signaling is required for angiogenesis and development of the placenta and cardiovascular system, and deletion of HIF-1α is embryonic lethal [8, 66]. Hypoxia is also required for the production and delamination of neural crest cells, discussed earlier, and this process is normally limited by the maturation of the circulatory system [67]. In cancer, HIF signaling is involved in angiogenesis, invasion, and metastasis [9, 68] as well as in maintenance of the CSC niche [6971].…”
Section: Microenvironmental Cues Shape Both Normal Development and Tumentioning
confidence: 99%